Modification of Multiple Stress Creep and Recovery Test Procedure and Usage in Specification - Golalipour, Amir (My University, 2011)
Since the emergence of Superpave equipment and specifications in the pavement industry in 1993, researchers and practitioners have found tools to understand characteristics and behavior of paving materials in better ways. Permanent strain or rutting is one of the most important pavement distresses. Due to its complexity and importance many studies were conducted to understand and alleviate this problem. Rutting or channeling can be classified as one of three types: 1) mechanical deformation (rutting) in subgrade or base, 2) plastic shear flow in asphalt layer and 3) wheel path consolidation (volume reduction) in asphalt layer. The plastic flow and volume consolidation of asphalt mixtures depends on a few factors, including the type of asphalt binder used in the mixture. It is believed that the accumulated strain in asphalt binder, as a consequence of traffic, is mainly responsible for the rutting of asphalt pavements (Phillips and Robertus, 1996; Sybilski, 1996). There have been attempts to formulate a specification parameter that can describe the affinity of a binder to the increase of accumulated deformation under periodic loading. The Dynamic Shear Rheometer (DSR) was introduced as tool to measure the binder contribution to rutting. In Superpave specification, it was assumed that rutting is caused by the total dissipated energy. The Superpave specification parameter |G*|/sin was identified as the term to be used for high temperature performance grading of paving asphalts in rating the binders for their rutting resistance (Anderson et al.,1994). Although used for many years as a rutting parameter, different researcher have shown the poor relationship between |G*|/sin and rutting. This term was found to be inadequate in describing the rutting performance of certain binders, particularly, the polymer modified ones. In the 9-10 project of National Cooperative Highway Research Program (NCHRP), researchers evaluated the direct correlation between mixture?s rutting properties and |G*|/sin on Rotational Thin Film Oven (RTFO) aged binders, tested at the same temperature at which the mixture Repeated Shear Constant Height (RSCH) test were conducted. They found a poor correlation between the mixture rate of accumulated strain and the parameter |G*|/sin measured at 10 rad/s (Bahia et al., 2001). In recent years many studies on bituminous binders have dealt with the inability of the original Performance Grade binder specification (PG) to correctly capture the performance properties of modified binders. Some agencies augmented the PG specifications with emperical, simple tests such as the elastic recovery, forced ductility, etc. and called it PG-plus. In addition to these, some more fundamentally correct tests such as the repeated creep and recovery (RCR) and multiple stress creep and recovery (MSCR) have been proposed. MSCR is a test that has received a lot of attention and significant acceptance by experts but still there is ongoing dialogue about shortcomings of this test. Some of these concerns are related to number of cycles and stress levels used in this test. Besides the testing protocol, binder selection criteria that is being proposed to reduce permanent deformation in asphalt mixtures under service load is of concern to many agencies due to the stress levels selected, relation to actual traffic speed, and traffic volume. This research attempts to factually address the relevance of these concerns and propose measures and procedures to rectify them with a particular consideration of changes to the current MSCR test and criteria. This study includes analysis of results for binders and mixtures collected to show the role of binders in mixtures' rutting resistance and the effects of temperature, stress level, and number of cycles. The research shows that the 10 cycles in the test are not sufficient to reach a stable secondary creep and a higher stress level will be useful to characterize modified binder behavior more clearly. A relatively simple nonlinear viscoelastic model is available (Delgadillo et al., 2011) and experimental results show that it can be used to estimate binder response to changing temperatures, loading time, and stress level. This model can be used for a more efficient selection of criteria for selecting binders in practice.